Maintenance Management Study to Building Near the Coastal Area - Muhammad Luqman bin Hairuwan (Progress in Engineering Application and Technology, 2023)
We may not be aware but coastal construction is different from inland construction. Buildings in the coastal environment are different from buildings in the inland. The maintenance of buildings in water or coastal areas is different from the maintenance of buildings on land. This is because the humid sea air and high salt levels can erode buildings quickly. Due to higher loads and extreme conditions, these coastal structures are expensive to design, build, maintain, repair, and insure. The objective of this study is to determine the cause and effect of salt attack and to study the importance of building maintenance in the ocean area. Questionnaire surveys were selected as a means of achieving the third objective of this survey. Use the appropriate sampling strategy to select enough samples that can represent the population. A survey questionnaire is created to collect input for the final questionnaire. The reliability recommendations then apply to the final questionnaire. The research method is very important in determining the purpose of the research. After identifying the survey data and purpose, we created a questionnaire. In addition, the number of questionnaires provided to residents should be proportional to the research goals.